2020
DOI: 10.2147/ijn.s237334
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electrospraying Oxygen-Generating Microparticles for Tissue Engineering Applications</p>

Abstract: Background: The facile preparation of oxygen-generating microparticles (M) consisting of Polycaprolactone (PCL), Pluronic F-127, and calcium peroxide (CPO) (PCL-F-CPO-M) fabricated through an electrospraying process is disclosed. The biological study confirmed the positive impact from the oxygen-generating microparticles on the cell growth with high viability. The presented technology could work as a prominent tool for various tissue engineering and biomedical applications. Methods: The oxygen-generated microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…This is a further indication the effect these stabilizing groups can have on hydrophobic polymer, bringing a change in the overall output in the form of the type of species one can produce—particles or fibers. This result could be associated with selected applied electrical field and solution parameters during the ES process as previously described from our group elsewhere [ 13 , 14 ]. Particle size distribution analysis indicated that all samples have average sizes between 1 and 10 μm.…”
Section: Resultsmentioning
confidence: 90%
“…This is a further indication the effect these stabilizing groups can have on hydrophobic polymer, bringing a change in the overall output in the form of the type of species one can produce—particles or fibers. This result could be associated with selected applied electrical field and solution parameters during the ES process as previously described from our group elsewhere [ 13 , 14 ]. Particle size distribution analysis indicated that all samples have average sizes between 1 and 10 μm.…”
Section: Resultsmentioning
confidence: 90%
“…Adding CaO 2 at 8-12 mg/mL concentration within gelatin/hyaluronan matrix enabled the fabrication of sprayable hydrogel dressings with prolonged oxygen-releasing capacity (2 weeks), antibacterial properties, and an important ability to diminish the metabolic stress and reduce cell death in hypoxic fibroblasts [135]. Given their extended-release oxygen profile, CaO 2 -loaded polyester microspheres (either solitary or encapsulated within a self-polymerized peptide hydrogel) exhibited long-term beneficial effects on normal cells [136,137]. An oxygen-generating implantable material consisting of alginate beads encapsulating CaO 2 and catalase has been developed by Huang and colleagues [138] as an active carrier for doxorubicin, with the aim to increase the drug sensitivity in cancer cells undergoing hypoxia-induced chemo-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CaO 2 particles can be coated with biodegradable polyesters such as poly(ϵ-caprolactone) (PCL) or poly (lactic- co -glycolic acid) (PLGA) to control and obtain a sustained release of O 2 . Additionally, alternate strategies to prolong O 2 release can be explored, such as other oxides (e.g., zinc oxide, manganese dioxide) and peroxides (e.g., magnesium peroxide, H 2 O 2 ), perfluorocarbons, and percarbonates ( 29 , 41 , 56 58 ).…”
Section: Discussionmentioning
confidence: 99%